ANA’S SUBMISSIVE BEHAVIOR IN E. L JAMES’ FIFTY SHADES OF GRAY - Didik Ardianto (LITERA KULTURA : Journal of Literary and Cultural Studies, 2021)
Submissive is a passive behavior that is the opposite of dominance. In regards to BDSM (stands for bondage, domination/discipline, submission/sadism and, masochism), submissive can be interpreted as submission for sadism in sexual activities displayed by the dominant partner. The submissive behaviors were also depicted a novel written by E. L James entitled Fifty Shades Of Gray. This research adopted the theory of love by Jacques Lacan. This research revealed the reason behind Ana's submissive behaviors whether she did because of love or because of being manipulated. Thus, with help of the BDSM perspective, this research also showed the depiction of Ana's submissive behaviors. The brief introduction of this research was related to how the character named Ana in E. L James' Fifty Shades of Gray portrayed as a submissive woman who was willing to experience sexual sadism done by Christian as the dominant partner. She had been trying to find her reason of submissive behaviors. Therefore, this research is also aimed to find the link between feeling in love and submissive behaviors. Keywords :Submissive, BDSM, love, dominance, sadism, masochism